Genetically modified organism: definition and finality - Cacciabaudo, F.; Altomare, R.; Gioviale, M. C.; Tomasello, Giovanni; Bruno, Antonio; Palumbo, Vincenzo Davide; Damiani, Provvidenza; Lo Monte, Attilio Ignazio (Progress in Nutrition, 2014)
Article 2 of the European Directive 2001/18/EC defines a genetically modified organism (GMO) a san organism in which the genetic material has been altered in a way that does not occur naturally by inserting DNA fragments from one organism’s gene into the chromosomes of another, changing its genetic expression. In the field of animal and plants biotechnology there are different application areas of genetic engineering such as improving the quantity and quality of agricultural production, pharmaceutical production in more sustainable ways or applications in environmental field.